CROSS-CULTURAL COMMUNICATION COURSE AS A FORM OF INTERNATIONALISATION AT HOME WITHIN RUSSIAN HIGHER EDUCATION INSTITUTIONS - Makeeva, Elena; Lopukhova, Yulia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Internationalisation of higher education at home is a relatively new phenomenon for Russia but, as a concept, it is one that is both broad and variable. The internationalisation of higher education at home has been influenced by the globalisation of economies and societies and the increased importance of knowledge. It is driven by a dynamic and constantly evolving combination of political, economic, socio-cultural and academic rationales. These motives take different forms and dimensions in different regions, in institutions and within their educational programmes. This study covers an intensive course named “Cross-cultural Communication” and its impact within Tempus, Erasmus+ and other funding programmes as well as traditional content of this course. The content of the course is evaluated through several approaches. The starting point is to consider how particular courses are taken into account in long-term strategies of universities, and on the other hand, how these intensive courses advance the implementation of internalisation strategies. Another approach concerns internationalisation at home and helps find out how, specifically, intensive courses advance internationalisation. The next point covers education and teaching development and shows what role particular courses have in the transfer of teaching methods, materials and whole course concepts in Russian higher education institutions.